REKONSTRUKSI HAKIKAT PENDIDIKAN AGAMA ISLAM: ANALISIS PERSPEKTIF AL-QUR'AN, HADIS, DAN PEMIKIRAN PENDIDIKAN ISLAM - Nurhabibah Nurhabibah; Haidar Putra Daulay; Muhammad Roihan Daulay (STKIP Pesisir Selatan, 2026)
Objective: This study aims to reconstruct the essence of Islamic Religious Education (IRE) based on the perspectives of the Qur'an, Hadith, mufassirun (Qur'anic exegetes), and muhaddithun (Hadith scholars), and to formulate its relevance in addressing contemporary challenges. Method: This research employs a qualitative approach through library research. Data were collected from the Qur'an, Hadith, classical and contemporary tafsir works, Hadith literature, and Islamic educational thought. The data were analyzed using content analysis and thematic interpretation. Results: The findings indicate that the essence of Islamic Religious Education extends beyond the transmission of religious knowledge. It encompasses ta'lim (instruction), tarbiyah (nurturing), ta'dib (character formation), and tazkiyah (spiritual purification) aimed at developing faith, knowledge, morality, intellectual competence, and social responsibility. The perspectives of the Qur'an, Hadith, mufassirun, and muhaddithun consistently emphasize the formation of insan kamil—a complete human being who fulfills the roles of servant of God and steward of the earth. In the context of globalization, Islamic education must integrate spiritual values, scientific literacy, ethical character, critical thinking, and digital competence. Novelty: This study offers an integrative reconstruction of the essence of Islamic Religious Education by synthesizing interpretations from Qur'anic exegesis, Hadith scholarship, and Islamic educational thought across different historical periods, resulting in a holistic and transformative educational framework relevant to contemporary society.